The Effectiveness of the Water Tepid Sponge to Decrease the Body Temperature in Children With Febrile Seizure - Fera Faradilla; Rusli Abdullah (Jurnal Kesehatan Pasak Bumi Kalimantan, 2020)
Abstract Background: Fever belongs to one of the triggers that resulted in febrile seizures. One of the actions of the non-pharmacological can be given to lower the body temperature in children with febrile seizure is the act of water tepid sponge. Purpose: this literature Review aims to analyze the effect of the adoption of the act water tepid sponge to decrease the body temperature in children who experienced febrile seizures. Methods: this Study explores quantitative evidence, published in electronic database such as Pubmed, Google Scholar, and Science Direct. With the use of search strategies, the researcher identified 39 articles that are potentially relevant to the purpose of the research, and 1 article included in the final analysis. Results: We can see a significant effect of decrease in body temperature in the group given the intervention water tepid sponge than a group of warm compresses. Conclusion: this Study shows that the actions of the water tepid sponge effective in lowering body temperature in children with febrile seizure. Keyword : Body temperature; Febrile seizures; Water tepid sponge.